American Public Opinion and U.S Foreign Policy. Case Study: the Aftermath of 9/11/2001 - Ghermaoui Amel (My University, 2009)
This Dissertation has the purpose of analysing the effect of American Public Opinion on U.S Foreign Policy after 9/11 dramatic events. Therefore, three important themes have been tackled in this work. 1) American public role Before 9/11 attacks, 2) The impact of 9/11 attacks on Americans’ attitudes towards U.S policy abroad, and 3) American public opinion on U.S military interventions in Iraq and Afghanistan and the role of the news media in the fight against terrorism. This work has mainly focused on American public ability to constrain U.S foreign policy, including U.S military interventions. Accordingly, a heated debate about American Public role in the U.S Foreign policy making has been presented and the instruments the American public uses in order to make the American government respond to its preferences.